An examination of the works of Dance Sinfonia by Dennis W. Fisher, Linden Lea, by Ralph Vaughan Williams, arranged by John W. Stout, Strawflower, by Ralph Hermann, Emperata Overture, by Claude T. Smith, and Foshay Tower Washington Memorial March, by John Philip Sousa, edited by Daniel Dorff - Knopp, Shawn Michael (Kansas State University, 2009)
This document is comprised of research and analysis of the comprehensive examination of the graduate conducting recital of Shawn Michael Knopp. This recital was performed by the Smoky Valley High School Concert Band, on February 27, 2009, at the Century II Concert Hall in Wichita, Kansas. The examined repertoire for the recital includes Dance Sinfonia, by Dennis W. Fisher, Linden Lea, by Ralph Vaughan Williams, arranged by John W. Stout, Strawflower, by Ralph Hermann, Emperata Overture by Claude T. Smith, and Foshay Tower Washington Memorial March by John Philip Sousa, edited by Daniel Dorff. This document contains theoretical and historical analysis and outlines the method of planning and preparing a graduate conducting recital according to the Blocher, Miles and Tracz formats.
Keywords: Dance Sinfonia; Linden Lea; Strawflower; Emperata overture; Foshay Tower Washington Memorial March; Education, Music (0522); Music (0413)